MANAJEMEN PELAYANAN PENDAFTARAN HAJI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN MANGGARAI TIMUR-NTT - Dwi Yuliana (Mudabbir: Jurnal Manajemen Dakwah, 2023)
this article investigates the Hajj registration service at the Office of the Ministry of Religion of East Manggarai Regency. In this study, the discussion will focus on service management issues and the supporting and inhibiting factors. This article is the result of field research using a qualitative approach. The data in this article were obtained through interviews, observation and documentation. Some of the important questions in this article are, what kind and how is the management of the Hajj registration service at the office of the Ministry of Religion in Kab. East Manggarai?, and secondly, what are the supporting and inhibiting factors for Hajj services at the office of the Ministry of Religion, Kab. East Manggarai? The results of this study indicate that the management of the Hajj registration service at the Office of the Ministry of Religion of East Manggarai Regency is that pilgrims must first open an account book, make a payment of 25 million rupiah for BPIH (Hajj Organizer), fill out the SPPH (Hajj Registration Letter form), and finally register with SISKOHAT (Integrated Hajj Computerized System). Meanwhile, the supporting and inhibiting factors in serving Hajj registration, namely the registration procedure assisted by management staff. And the inhibiting factor is the lack of technological knowledge that makes online registration difficult.